Over a million students use our free study notes to help them with their homework
When we complete the square, we're looking for an equation that looks like (x-a)2 + (y-b)2 = r2, where (a,b) is the centre and r is the radius. When we expand brackets usi...
3-1=2 2X2 = 4 2-1= 1 =3x^2- 4x
The function f(x) is a product of 2 functions of x, so when we differentiate it, we need to use the product rule.
The product rule states that for a function f(x) = g(x)*h(x), f'(x) is given by g(x...
Integrate this = (3x^3)/3 + (3x^2)/2 + c So y = x^3 + (3x^2)/2 + c Using point (0,0), 0 = 0 + 0 + c so c = 0. Full equation of the curve is therefore x^3 + (3x^2)/2
Can show working on a whiteboard.
←
367
368
369
370
371
→
Internet Safety
Payment Security
Cyber
Essentials